DAN Annual Diving Report 2018 Edition: A Report on 2016 Diving Fatalities, Injuries, and Incidents - Buzzacott, Peter (2019)
The 2018 DAN Annual Diving Report is a summary of recreational scuba diving and freediving incidents, injuries and fatalities that occurred in 2016 in the U.S. or Canada or that involved U.S. or Canadian residents. DAN’s intention is for this annual publication to enhance awareness of dive injuries and give divers the insights they need to better avoid emergencies. DAN received notification of 169 deaths involving recreational scuba diving in 2016. The largest numbers of reported fatalities occurred in Florida and California, with 20 and 7 fatalities respectively. The geospatial distribution of the reported fatalities by region is: 72 in North America, 27 in Europe, 23 in Oceania, 19 in the Caribbean, 18 in Asia, 4 in South America, and 1 each in Northern Africa, Southern Africa, the Middle East and Central America. The location was unknown in two cases. Diving injury data analyzed in this report comes mainly from DAN’s Medical Services Call Center (MSCC) and its annual survey of hyperbaric chambers. Section 2, Diving Injuries, categorizes the types of injuries managed by DAN Medical Services and includes summaries of actual cases. In 2016, there were 10,320 calls or emails to the MSCC from divers who needed assistance, information or consultation; 59% of these cases were dive-related, and 41% were not. The most common dive-related health issues discussed during these calls were barotrauma, decompression sickness and marine envenomations. The Diving Incident Reporting System (DIRS) collects diving incident reports through the DAN website, www.DAN.org. Divers worldwide are encouraged to report any incidents that occur during dives via this system. Of the 102 incidents reported in 2016, 91 involved open-circuit scuba diving, 5 involved rebreather diving, and 6 involved breath-hold diving. In addition to the injury surveillance data collected by DAN in Durham, North Carolina, additional injury surveillance data analyzed in this report was contributed by DAN-affiliated agencies and other organizations around the world. Section 5 features reports from DAN Europe, DAN Japan and DAN Asia Pacific. Other organizations that reported their findings were the British Sub-Aqua Club (BSAC), New Zealand Underwater Association, the Irish Underwater Council and the Underwater Council of British Columbia. Although scuba diving accidents can be fatal, many can be prevented with safe diving practices and by understanding how to identify hazards and avoid or mitigate the risks that cause accidents. The DAN Hazard Identification and Risk Assessment Program enables divers and dive operators to recognize and avoid these risks; this program is described in Appendix B: DAN Operational Safety Programs. DAN exists to provide divers with the resources they need to make every dive accident- and injury-free. When accidents cannot be prevented, DAN is here to provide divers with emergency assistance no matter where in the world they are. With the support of all the DAN offices and contributors worldwide, DAN is committed to providing resources that will resonate with and be useful to divers everywhere.